2016
DOI: 10.4244/eijv12i1a6
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with everolimus-eluting bioresorbable vascular scaffolds for treatment of patients presenting with acute myocardial infarction: a propensity-matched comparison to metallic drug eluting stents 18-month follow-up of the BVS STEMI first study

Abstract: STEMI patients treated during the early experience with BVS had similar acute angiographic results as compared with the EES group. Clinical midterm follow-up data showed a higher clinical events rate compared with metal stents. The majority of clinical events occurred in the early phase after implantation and mainly in cases without post-dilatation. Optimisation of the implantation technique in the acute clinical setting is of paramount importance for optimal short and mid-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 24 publications
1
9
0
1
Order By: Relevance
“…1.3%, p = 0.05) [32]. Interestingly, the 30-day MACE rate in BVS patients without postdilatation was 6.8% and 3.6% in patients with post-dilatation.…”
Section: Discussionmentioning
confidence: 81%
“…1.3%, p = 0.05) [32]. Interestingly, the 30-day MACE rate in BVS patients without postdilatation was 6.8% and 3.6% in patients with post-dilatation.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, the ABSORB II trial demonstrated an ongoing risk of ScT through 3 years of 3% . In addition, increased incidence of ScT of up to 3% at 24 months follow‐up has been reported in patient cohorts reflecting daily clinical practice . The randomized AIDA trial, confirmed the increased risk of ScT in patient reflecting daily clinical practice, with 3.5% definite or probable device thrombosis in the Absorb arm and 0.9% in the Xience arm .…”
Section: Introductionmentioning
confidence: 86%
“…In brief, the common inclusion criteria for this study are patients who had received a single BRS or CoCr EES that are 28 mm in length in long coronary lesions. The patients in the BRS group are selected from the BVS Expand [ 8 ] and BVS STEMI [ 9 ] registries which are single centre prospective observational registries conducted at Thorax Centre, Erasmus Medical Centre that evaluates the long term safety and performance of the BRS-absorb coronary stent in routine clinical practice post market registration. Informed, written consent was obtained from the patients before they undergo any procedure.…”
Section: Methodsmentioning
confidence: 99%